Effect the Annealing on The Growth Length Rate of Alpha Particles Tracks in CR-39 Nuclear Track Detector - Rasha wael; Mushtaq Al-Jubbori (College of Education for Pure Sciences, 2023)
The aime of this paper is to investigate the impact of annealing on track growth  rate (dL/dt), which is calculated using the track length measurement method. A 600 micro meter-thick CR-39 detector, divided into four samples (1 x 1 cm2), was  vertically irradiated by alpha particles with 2.6 MeV from a 241Am source which have max energy 5.48 MeV . The three samples were annealed at 100-140oC  by type 20o C  using oven Memmert U4079142. All samples were etched in a 6.25 N NaOH solution at 70±1 oC in a Memmert W200 water bath, the periodic etching time was 0.5 hours to 6  hours. The etched image was captured using a camera (MADC_5A) attached to a microscope (XSZ-H Series Biological Microscope). The bulk etch rate and diameters increase with increasing annealing temperatures. The new method used in this paper to calculate the experimental track length is based on the relation between track length and track diameter obtained from track-test software.